Effects on the radiation pattern of a reflector antenna due to a dust accretion on its surface - Hamed, Sameir M. Ali; Musa, Abdulwaheed; Bashir, Saad Osman (IEEE, 2015)
The performance of the reflector antenna may seriously degrades in terms of the gain reduction and beam shift when a dust/sand is accreted on its surface. This paper investigates the effects on the radiation pattern of a practical parabolic reflector antenna due to the dust accretion on its surface. A modified far-fields expressions for a parabolic reflector that is fed by a rectangular waveguide and partially covered with a uniform layer of dust are formulated. These modified field expressions are used to study the radiation pattern of a reflector antenna of 1 m in diameter which is fed by a rectangular waveguide of sides 0.95λ×0.70λ operating at X-band, assuming an acretion of a uniform layer of dust on the reflector. It is found that the reduction of the maximum signal level at a given frequency changes almost periodically with a period nearly equal to π as t increases, and the thick layers of dust does not necessarily result in more reduction in the signal level or beam phase shift compared to the thin layers. For t=6 mm, the worst signal reduction and phase shift in the main beam occur when the surface of the reflector is half-covered with dust, while the full-covered reflector results in a minimum signal reduction without any phase shift in the main beam.